CYTOGENETICS OF 4 BRAZILIAN HYLA SPECIES (AMPHIBIA-ANURA) AND DESCRIPTION OF A CASE WITH A SUPERNUMERARY CHROMOSOME - Baldissera, F. A.; Deoliveira, PSL; Kasahara, S. (Soc Brasil Genetica, 1993)
The chromosomes of Hyla fuscovaria, H. hayii and II. prasina, with 2n=24, and of Hyla sp. (aff. circumdata), a new species, with 2n=24 and 2n=25, were studied.The karyotypes with 2n=24 in the four species were very similar, with almost no differences in the size and morphology of the chromosomes. The numerical variability found in Hyla sp. (aff. circumdata) is due to the occurrence of a supernumerary chromosome in some specimens. NOR data obtained for the first time in the four species and C banding analysis of H. prasina indicate that such types of banding may be useful to differentiate species with very similar karyotypes, contributing to the understanding of chromosome evolution and the establishment of phylogenetic relationships among Brazilian Hyla species.